Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

Comparative metabolomics reveals distinct metabolic profiles and in vitro activities of fermented noni juice from Samoa and China's Hainan - Qianjin Ni; Meimei Nie; Linlin Han; Mingfei Gu; Lingming Xiong; Yayuan Xu; Lei Feng; Liying Niu; Runqiang Yang; Dajing Li; Zhuqing Dai (Food Chemistry, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Heterogeneous reaction of NO2 with hydroxyapatite particles: Effects on phosphorus water solubility - Linlin Ye; Yan Huang; Linfeng Zhang; Panya Xu; Jingjing Wang; Chengzhu Zhu; Tong Zhu; Mingjin Wang (Atmospheric Environment, 2026)

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

Comparative precipitation forecasting in the Northeastern Tibetan Plateau: Tree-ring reconstruction and future projections using machine learning and CMIP6 models - Longyun Ma; Haoyuan Xu; Jinjian Li; Zeyu Zheng; Linlin Cui; Caihong Liu; Shanlei Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Unique coordination of four-metal-atom clusters on C5N2H2 boosts nitrogen reduction reaction performance: a DFT study - Linlin Li; Shaopeng Xu; Yan Yan; Mengmeng Wang; Yan Chen; Jiaojiao Chen; Wei Li; Xunlei Ding (Fuel, 2026)

Spatial heterogeneity of ice phenology in large lakes of Xinjiang, China - Kangzheng Zhong; Jiaxin Hao; Puzhe Huo; Chunpeng Chen; Linlin Cui; Liping Xu; Zhijun Li; Jiang Li; Guanghui Wei (Regional Environmental Change, 2026)

Experimental investigation on the squeeze deformation and failure mechanisms of tunnel invert in high ground stress stratified soft rock and directional reinforcement measures - Wenbo Yang; Linlin Yang; Zhongyuan Xing; Wenyu Xu; Chaofan Yao; Fangyin Wu; Yuxiang Huan (Tunnelling and Underground Space Technology, 2026)

Retraction notice to “Study on the effect of SDBS and SDS on deep coal seam water injection” [Sci. Total Environ. 856 (2023) 158930] - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2026)

Unveiling urban process-dependent hydrological responses via rainfall “fingerprints” - Ting Liu; Lina Yuan; Yuying Li; Zijiang Song; Linlin Ye; Ao Xu; Tsering Namgyal; Chao Li; Min Liu (Journal of Hydrology, 2026)

Hydrothermal response to changes in snow and vegetation cover in Xinjiang, China - Huimin Yang; Yuehong Ran; Yichi Xu; Lihong Wang; Linlin Cui; Xiangqian Li; Mengwen Peng (Journal of Environmental Management, 2026)

Geographically-weighted weakly supervised Bayesian High-Resolution Transformer for 200 m resolution pan-Arctic sea ice concentration mapping and uncertainty estimation using Sentinel-1, RCM, and AMSR2 data - Mabel Heffring; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Co-combustion of municipal solid waste and antibiotic fermentation residue: Gaseous pollutant emissions and ash slagging characteristics - Changhong Huang; Yuhang Du; Lei Bei; Jiaxing Du; Wu Yang; Ben Wang; Linlin Xu; Lushi Sun (Fuel, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

Breakage mitigation optimization strategy for a spiral-groove wheel fertilizer distributor based on a controlled-release fertilizer breakage model - Hongjian Zhang; Xiubo Chen; Xinpeng Cao; Yongxian Wang; Xin Han; Junshuo Xu; Linlin Sun; Jing Wang; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Source-sink dynamics of WADA-prohibited compounds in coastal urban aquatic environments: From WWTP to bay - Min Zhou; Zifan Weng; Linlin Zhang; Shen Yu; Bing Hong; Yuxin Chen; Zhixing Yang; Qian Sun; Tao Ma; Dunming Xu (Journal of Environmental Management, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Extreme warming and pulsed volcanism during the Paleocene-Eocene Thermal Maximum - Abdelhamid M. Salman; Xue-Ting Wang; Zuoling Chen; Linlin Cui; Hongwei Li; Xu Wang (Science China Earth Sciences, 2026)

Impact of environmental factors on the distribution characteristics of phytoplankton functional groups in Beijing - Linlin Qin; Xu Han; Ting Zhu; Yixuan Zhang; Na Cui; Yuepeng Liu; Wenyan Liang (Protist, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Sorption of Se(IV) and Sr(II) onto granite fracture-filling materials: effects of mineral compositions, co-presence, pH, and ionic strength - Ziqi Ma; Yueying Bi; Jiuhong Xu; Linlin Qi (Journal of Environmental Management, 2026)

Nitrogen cycle suppression and enhanced carbon burial during the Paleocene-Eocene thermal maximum, recorded from Tarfa section, Egypt (Tethys Ocean) - Abdelhamid M. Salman; Xueting Wang; Zuoling Chen; Hongwei Li; Linlin Cui; Nageh A. Obaidalla; Xu Wang (Global and Planetary Change, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

A first quantitative assessment of seabed litter collection efficiency using bottom otter trawls and fishery depletion models - Yue Chen; Xinxing You; Linlin Gao; Huaxiang Sheng; Yipu Sui; Xinle Xu; Liuyi Huang (Environmental Pollution, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

Nanopore-Based Full-Length Transcriptome Sequencing: In-Depth Exploration of Green Sea Turtle (Chelonia mydas) Genome - Qi Huang; Yongjun Sun; Linlin Zhao; Wenbo Zhu; Fei Shao; Jin Xu; Yongjian Qin (Fishes, 2026)
The green sea turtle (Chelonia mydas), a widely distributed species, plays a crucial role in maintaining the marine ecosystem. However, studies on C. mydas require accurate and comprehensive genome annotation information. Long-read direct transcriptome data of C. mydas were obtained using direct RNA sequencing on the Oxford Nanopore Technologies (ONT) platform from blood tissue of a single captive individual. A total of 4061 novel transcripts were obtained by comparing long-read direct transcripts with genome annotation of C. mydas. We also predicted 2402 CDSs on the novel transcripts. Among them, 1208 (50.29%) had functional annotation information in the databases. In addition, we predicted and analyzed AS events, fusion transcripts, methylation sites, poly(A)s, and lncRNAs in the C. mydas long-read direct transcriptome. Overall, our study provides the a long-read direct blood transcriptome for C. mydas to complement and improve its genome annotation. This valuable resource will contribute to future research on C. mydas. Additionally, the analyses of transcriptome structure mentioned above may provide new insights and ideas for the study of C. mydas.

Quantitative identification of anthropogenic sources of metal(loid)s in river sediments from a small watershed based on APCS-MLR and MixSIAR model - Yao Wei; Fen Xu; Qiang Liu; Chunmei Jiang; Linlin Bao (Marine Pollution Bulletin, 2026)

Efficient hydrogenation of heavy turpentine into high-energy-density biofuel over MOF-derived nano-Ni@C/rGO and associated kinetic insights - Xiaoying Tang; Yongxiong Yang; Ying Tang; Shen Luo; Xiaopeng Chen; Xu Wei; Linlin Wang (Journal of Environmental Chemical Engineering, 2026)

Carbon dots/konjac glucomannan/starch anti-freezing gel: development and cryoprotective coating for beef preservation - Linlin Zhao; Zeyue Zhao; Wenqin Gu; Huinan Jiang; Hao Xu; Suqing Sun; Xiangren Meng (Food Research International, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

Eco-friendly asphalt: Emission reduction and performance enhancement with a novel fume suppressant - Shangheng Zeng; Ghim Ping Ong; Shi Xu; Hongyue Liu; Linlin Liu; Jianying Yu (Transportation Research Part D: Transport and Environment, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Effects of Lactiplantibacillus plantarum and Staphylococcus simulans fermentation on Maillard reaction and flavor characteristics in a myofibrillar protein-glucose reaction system - Xuefei Shao; Huhu Wang; Xiangyu Song; Xue Gong; Linlin Cai; Xinglian Xu (Food Chemistry, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

A nanoengineered strategy combining deep oxygenation and immunogenicity regulation to unleash the power of anti-tumor immunity - Gang Cheng; Linlin Tao; Nian Huang; Xiaoxiao Hu; Mengmeng Yang; Fangnan Lv; Nan Yang; Siyuan Meng; Zuhang Xing; Boyu Gu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Seasonal-spatial distribution and prevailing wind analysis of Martian dust devils in Amazonis Planitia using a multi-scale attention network - Linlin Shi; Gan Liu; Jialong Lai; Xu Ma; Feifei Cui; Xiaoping Zhang; Yi Xu; Qiquan Yang (Science China Earth Sciences, 2026)

Ecological niche shapes the composition and function of microbial communities in Astragalus membranaceus - Xiao Chen; Zhengyan Li; Yaogong Zhang; Chao Yao; Yuanshuai Yu; Feifei Ding; Jingyi Xu; Yuan Li; Linlin Dong; Guangfei Wei (Plant and Soil, 2026)

Intelligent Recognition Network for Difficult Airway Based on Multi-View Input and Attention Aggregation - Fan Zhang; Jiaqiang Zhang; Zhaoxiang Zhang; Ke Yang; Linlin Zhao; Yuelei Xu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

sRNA networks as molecular switches: Decoding foodborne bacterial pathogen adaptation from farm to fork to clinic and prospects for next-generation precision interventions - Linlin Cai; Huhu Wang; Yunting Xie; Xinglian Xu; Guanghong Zhou (Trends in Food Science & Technology, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

Iron-induced charge density redistribution of medium entropy alloys for ampere-level seawater electrolysis - Luyu Liu; Xiang Ding; Jun Xiang; Haotian Qin; Siyuan Tang; Linlin Xu; Jianling Dong; Yin Yin; Nan Jiang; Xinchun Yang; Fuzhan Song (Fuel, 2026)

An integrated multiscale computational study of nephrotoxicity mechanism of citrinin and its metabolites (CIMs)：density functional theory, network toxicology, and molecular dynamics simulation - Jiaxing Li; Furong Xue; Linlin Xu; Huijing Zhang; Xizi Zhang; Chenchen Qi; Chengtao Wang; Wei Chen; Di Zhang (Mycotoxin Research, 2026)

Involvement of ARTS in bisphenol A-induced apoptosis of mouse Leydig cells - Ying Yang; Si Yang; Meijuan Zhang; Linlin Xu; Jiaxiang Chen (Toxicology, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Ptbp2 Alleviates Neuroinflammation and Blood–brain Barrier Disruption via Modulating Microglial Polarization in Ischemic Stroke - Wenting Xu; Linlin Li; Mengjia Zhou; Cong Zhang; Xiangjian Zhang (Molecular Neurobiology, 2026)

Effect of cAMP concentration on apoptosis of sheep granulosa cells in vitro - Wenhao Wang; Linlin Pei; Peilin Guo; Andi Qiao; Shuyan Guo; Xin Xu; Chunjie Liu (In Vitro Cellular & Developmental Biology - Animal, 2026)

prepIMS: a robust data preprocessing workflow for ion mobility mass spectrometry imaging - Linlin Wang; Chengyi Xie; Lei Guo; Thomas Ka Yam Lam; Chris Kong Chu Wong; Mudassir Shah; Xiangnan Xu; Jianing Wang; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2026)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

Study on slow pyrolysis mechanism of non-metallic fractions in waste printed circuit boards using TG-FTIR-MS analysis - Lushi Sun; Gan Wan; Tao Chen; Jiaxing Du; Linlin Xu; Haitao Liu (Journal of Environmental Management, 2025)

Aminated lignin-modified polyethersulfone membranes with enhanced antifouling performance for oil-water separation - Linlin Liang; Meijiao Peng; Hui Xu; Zijun Wu; Baojie Liu; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Journal of Environmental Chemical Engineering, 2025)

Mitochondria-targeted nanoparticles with whole-course-repair efficacy in therapy of myocardial ischemia reperfusion injury - Xiya Wang; Hang Chen; Pingyuan Sun; Linlin Zhao; Renxiang Gui; Xu Wang; Emeli Chatterjee; Jiahong Xu; Jianle Chen; Xuerui Chen (Chemical Engineering Journal, 2025)

Pilot-scale investigation of polyhydroxyalkanoates synthesis using mixed microbial cultures from fermented thermally hydrolyzed sludge - Yun He; Kuixiao Li; Yu Zhang; Gang Wang; Jing Chang; Shan Hao; Linlin Wei; Xu Xing (Bioresource Technology, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

OWTDNet: A Novel CNN-Mamba Fusion Network for Offshore Wind Turbine Detection in High-Resolution Remote Sensing Images - Pengcheng Sha; Sujie Lu; Zongjie Xu; Jianhai Yu; Lei Li; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2025)
Real-time monitoring of offshore wind turbines (OWTs) through satellite remote sensing imagery is considered an essential process for large-scale infrastructure surveillance in ocean engineering. Current detection systems, however, are constrained by persistent technical limitations, including prohibitive deployment costs, insufficient discriminative power for learned features, and susceptibility to environmental interference. To address these challenges, a dual-branch architecture named OWTDNet is proposed, which integrates global contextual modeling via State Space Models (SSMs) with CNN-based local feature extraction for high-resolution OWTs detection. The primary branch utilizes a Mamba-structured encoder with linear computational complexity to establish long-range spatial dependencies, while an auxiliary Blurring-MobileNetv3 (B-Mv3) branch is designed to compensate for the local feature extraction deficiencies inherent in SSMs. Additionally, a novel Feature Alignment Module (FAM) is introduced to systematically coordinate cross-modal feature fusion between Mamba and CNN branches through channel-wise recalibration and position-aware alignment mechanisms. This module not only enables complementary feature integration but also enhances turbine-specific responses through attention-driven feature modulation. Comprehensive experimental validation demonstrated the superiority of the proposed framework, achieving a mean average precision (AP) of 47.1% on 40,000 × 40,000-pixel satellite imagery, while maintaining practical computational efficiency (127.7 s per image processing time).

Gaussian Building Mesh (GBM): Extract a building’s 3D mesh with Google Earth and Gaussian Splatting - Kyle Gao; Dening Lu; Hongjie He; Liangzhi Li; Linlin Xu; Michael A. Chapman; Jonathan Li (Remote Sensing Applications: Society and Environment, 2025)

Mbnl1 Protects Against Cerebral Ischemia–Reperfusion Injury by Modulating Microglia/Macrophage Polarization via NF-κB Pathway - Wenting Xu; Mengjia Zhou; Linlin Li; Yuqing Zhang; Tianya Zhang; Xiangjian Zhang (Molecular Neurobiology, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Predicting seasonal distribution and inter-seasonal migration corridors for three subspecies of common minke whales - Linjie Li; Linlin Zhao; Shiji Xu; Changdong Liu; Yanli Tang (Ocean & Coastal Management, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

A nano-pesticide with low toxicity for earthworms obtained by immobilizing avermectin onto Mg/Al layered double hydroxides - Linlin Shi; Fengshou Dong; Jun Xu; Xiaohu Wu; Yongquan Zheng; Xinglu Pan (Environmental Pollution, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

The regulation of gut microbiota and urate lowering: A study on the mechanisms of action of probiotics and plant components - Zhihua Xing; Yue Xu; Wen Jiang; Mingyu Gao; Guanghuan Shen; Yingjie Liu; Na Ling; Linlin Cui (PharmaNutrition, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Impacts of output-based ETS and subsidies on CCS retrofitting in China’s coal-fired power plants - Changsheng Yi; Linlin Xu; Yaling Tian (International Journal of Greenhouse Gas Control, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Melatonin Promotes Cerebral Angiogenesis in Ischemic Mice via BMP6/Smad1/5/9 Pathway - Linlin Li; Yujia Yuan; Cong Zhang; Ying Li; Renhao Xu; Xiangjian Zhang; Wenyan Shang (Molecular Neurobiology, 2025)

High-pressure homogenization treatment on yeast protein: Effect on structure and emulsifying properties - Zihuan Wang; Xiuli Xu; Zhaoli Liu; Tong Xu; Linlin Ma; Fuhang Song (Food Research International, 2025)

Elucidating the pattern of flavor evolution during the steaming process of fermented sausages in two dimensions: Strain fermentation and steaming time - Xuefei Shao; Huhu Wang; Xiangyu Song; Na Xu; Linlin Cai; Xinglian Xu (Food Chemistry, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

SagMSI: A graph convolutional network framework for precise spatial segmentation in mass spectrometry imaging - Mudassir Shah; Linlin Wang; Lei Guo; Chengyi Xie; Thomas Ka-Yam Lam; Lingli Deng; Xiangnan Xu; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Mercury migration characteristics and the re-emission inhibition in seawater flue gas desulfurization system - Chuanwei Li; Gan Wan; Linlin Xu; Jiaxing Du; Lushi Sun; Li Lin (Journal of Environmental Chemical Engineering, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Dual-responsive gelatin/fucoidan-based membrane with colorimetric and control-released performance for meat freshness monitoring and preservation - Linlin Li; Haoran Wang; Yimeng Zhang; Wei Ji; Minmin Chen; Baocai Xu; Hualin Wang (Food Packaging and Shelf Life, 2025)

Development of a colorimetric sensor array with weighted RGB strategy for quality differentiation of Anji white tea - Qilin Xu; Xianggang Yin; Xinyi Huo; Xiaohan Zhao; Linlin Wu; Yifeng Zhou; Jun Huang (Journal of Food Engineering, 2025)

3D semantic segmentation: Cluster-based sampling and proximity hashing for novel class discovery - Jing Du; Linlin Xu; Lingfei Ma; Kyle Gao; John Zelek; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

From field to table: Reducing residual toxicity and risk of four pesticides via washing and blanching of cowpea (Vigna unguiculata (L.) Walp.) - Shuangwei Zhang; Yajing Guo; Shanshan Zhu; Linlin Guo; Xinglu Pan; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiaohu Wu (Food Chemistry, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

The dewatering performance of streptomycin mycelial residue promoted by the Fenton process synergistic with biochar - Lushi Sun; Jiaxing Du; Xingxing Zhou; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Management, 2025)

Rational design of micro-cone array on copper host for dendrite-free sodium metal plating - Mengyang Xu; Chengwen Gao; Tsz Wing Tang; Linlin Zhang; Jiawen You; Xing Zhou; Mengjia Xu; Jang-Kyo Kim; Zhengtang Luo (Chemical Engineering Journal, 2025)

An experimental study of heat transfer in pulsed fluidised beds via infrared thermography - Shuxian Jiang; Linlin Xu; Kaiqiao Wu; Victor Francia; Marc-Olivier Coppens (Chemical Engineering Journal, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Seasonal spatial distribution patterns of AmphiOctopus ovulum in the East China Sea: current status future projections under various climate change scenarios - Linlin Yang; Min Xu; Yan Cui; Shuhao Liu (Frontiers in Marine Science, 2025)
Currently, there is also little up to date information on the the current population status and life history traits of AmphiOctopus ovulum , a very often seen cephalopod species in the East China Sea. It is therefore important to figure out the seasonal spatial distribution of this species, both in terms of number and biomass, and the environmental variables which determine them. Additionally, climate change plays an important role in determining the characteristics of individual species and thus on the ecosystems they inhabit. We set out to understand the responses of A. ovulum to habitat variables and to make projections based on the climate change scenarios described in the IPCC’s SSP1-2.6 and SSP5-8.5 criteria. We carried out seasonal bottom trawling surveys in the East China Sea region during 2018 and 2019 to fill this knowledge gap. Our results showed that the average individual size values ranged from 17.80−43.00 g·ind -1 in spring and 23.49−33.00 g·ind -1 in summer; the measured sea bottom temperature, sea bottom salinity, and depth value ranges were 10.81−27.06°C, 31.73–35.25‰, and 91–103 m independently in spring to winter. Our study showed that A. ovulum was distributed in the area between 27°–29°N, 122.5°–125°E during spring to autumn, and expanded into the area between 26.5°–32.5°N, 121°–124.5°E in winter. The core habitat of A. ovulum was centered on the area between 27.5°–28°N, 122.5°–123.5°E, and can be expected to expand to the northeast and southwest independently under the most likely global warming scenarios. Our results will benefit the development of suitable conservation measures for cephalopod habitats, and incorporate the impacts of climate change into fisheries management programs.

Current and future thermal effects and spatial optimization modelling of urban greenspace in megacity - Rundong Feng; Shenghe Liu; Fuyuan Wang; Bin Chen; Kaiyong Wang; Linlin Xu (Sustainable Cities and Society, 2025)

The dewatering performance and mechanism of streptomycin mycelial residue based on Fenton oxidation - Linlin Xu; Xingxing Zhou; Jiaxing Du; Gan Wan; Lushi Sun (Process Safety and Environmental Protection, 2025)

Sustainable futures for transformational forestry resource-based city: Linking landscape pattern and administrative policy - Linlin Xu; Hu Yu; Linsheng Zhong (Journal of Cleaner Production, 2025)

Mercury (II) adsorption and gaseous mercury re-emission inhibition from seawater flue gas desulfurization (SFGD) wastewater by Fe-Cu bimetallic modified activated carbon - Lushi Sun; Gan Wan; Ke Tang; Linlin Xu; Li Lin (Fuel, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

A novel stochastic IDA-CSM based design framework of the externally-attached sub-system for seismic upgrading - Xu-Yang Cao; Dejian Shen; Kun Ji; Jiann-Wen Woody Ju; Linlin Xie (Bulletin of Earthquake Engineering, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

The impact of energy metabolic pattern on household carbon emissions: A spatio-temporal perspective in Guangdong-Hong Kong-Macao Greater Bay Area - Lei Chen; Jiahan Luo; Guotian Cai; Linlin Xia; Yongyang Wang; Linyu Xu (Sustainable Cities and Society, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

About 868 cal. yr BP tsunami event at the northern South China Sea revealed from offshore sediments - Yuming Wang; Xiaohong Chen; Adam D. Switzer; Linlin Li; Yang Xu; Yukun Wang; Elaine Tan; Peizhen Zhang (Global and Planetary Change, 2025)

Electronic engineering induced ultrafine non-noble nanoparticles for high-performance hydrogen evolution from ammonia borane hydrolysis - Siyuan Tang; Linlin Xu; Xiang Ding; Quanjiang Lv; Haotian Qin; Aosong Li; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

Characterization and genome analysis of Pseudomonas phages isolated from various sources related to chilled chicken - Haijing Hu; Linlin Cai; Liangting Shao; Xinglian Xu; Huhu Wang; Guanghong Zhou (Food Research International, 2025)

Spatiotemporal evolution of wildfire activity during the Paleocene-Eocene Thermal Maximum in China - Xue-Ting Wang; Zuoling Chen; Linlin Cui; Xu Wang (Science China Earth Sciences, 2025)

A 219-year tree-ring evidence revealing the influence of the Atlantic Multi-decadal oscillation on annual mean temperature in the northern Western Sichuan Plateau - Xu Wu; Jinjian Li; Linlin Cui; Xiaofei Wu; Kaiqing Yang; Alma Lorelei de Jesus (Climate Dynamics, 2025)

Effect of Feeding Mice Soluble Metals and Heavy Metal Contaminated Soil on Feces Metal Concentrations - Ningning Xu; Liping Li; James A. Ippolito; Weiqin Xing; Yale Wang; Baozhong Zhang; Yongqiang Yang; Ling Bai; Linlin Zhao (Biological Trace Element Research, 2025)

Indian summer monsoon variations since late MIS3: A perspective from multiproxy evidence from Lake Xingyun in southwestern China - Haiyang Yu; Linlin Cui; Xu Wang; Xueyun Ma; Bing Xu; Wubiao Li; Xueting Wang (Quaternary International, 2025)

Global distribution pattern and conservation of the cosmopolitan cold-water coral species Desmophyllum dianthus under climate change - Wenhao Huang; Zongling Wang; Fangyuan Qu; Chang Zhao; Miaozhuang Zheng; Zhaohui Zhang; Shenghao Liu; Qinzeng Xu; Xuelei Zhang; Linlin Zhao (Journal of Environmental Management, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

Distribution of microplastics in the soils of a petrochemical industrial region in China: Ecological and Human Health Risks - Yuting Guo; Rongshan Wu; Heng Zhang; Changsheng Guo; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2025)

An AIE-TICT fluorescence probe cascade responsive to H2S, polarity and viscosity to track microenvironment changes in cellular model of ischemia-reperfusion injury - Liguo Ji; Aoxiang Fu; Yuying Zhang; Ying Xu; Yanbei Xi; Shaoli Cui; Na Gao; Linlin Yang; Wanbing Shang; Zhijun Yang; Guangjie He (Analytica Chimica Acta, 2025)

Towards a dialectical understanding of rural resilience and rural sustainability: bibliometric analysis and evidence from existing literature and China - Huan Li; Tao Xu; Chen Yang; Yang Fu; Changyan Wu; Linlin Zhang; Guoliang Xu; Wei Wang (Environment, Development and Sustainability, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

N18 ring: A building block for constructing 1D and 2D polymeric nitrogen frameworks - Yuxiang Gao; Ying Zhang; Shuang Liu; Bo Jin; Linlin Guo; Xu Guo; Zhen Yao; Peng Wang; Bingbing Liu (Science Bulletin, 2024)

Individual tree species classification using low-density airborne multispectral LiDAR data via attribute-aware cross-branch transformer - Lanying Wang; Dening Lu; Linlin Xu; Derek T. Robinson; Weikai Tan; Qian Xie; Haiyan Guan; Michael A. Chapman; Jonathan Li (Remote Sensing of Environment, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Low level exposure to BDE-47 facilitates the development of prostate cancer through TOP2A/LDHA/lactylation positive feedback circuit - Linlin Tian; Nan Zhou; Ning Zhao; Mengkai Qiao; Min He; Ziqing Mao; Wenjiong Xu; Dandan Xu; Yan Wang; Yan Xu; Tong Chen (Environmental Research, 2024)

Precise fabrication and superior combustion properties of n-B pomegranate microspheres based on a new dissolution-dispersion-coating method - Yushu Xiong; Baoxuan Li; Yinghong Wang; Linlin Liu; Jie Huang; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

Advancing tea detection with artificial intelligence: Strategies, progress, and future prospects - Qilin Xu; Yifeng Zhou; Linlin Wu (Trends in Food Science & Technology, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Exploring the paradox of densification and greening in China’ s old cities - Wenqi Chen; Yuxuan Qiu; Linlin Ruan; Chun Ren; Chunfeng Zhou; Sucheng Xu; Kechao Wang; Tingting He; Wu Xiao (Urban Forestry & Urban Greening, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

Water-dependent effects of biodegradable microplastics on arsenic fractionation in soil: Insights from enzyme degradation and synchrotron-based X-ray analysis - Kailin Gong; Tianzi Liu; Cheng Peng; Ziyi Zhao; Xiang Xu; Xuechun Shao; Xuan Zhao; Linlin Qiu; Wenwen Xie; Qian Sui; Wei Zhang (Journal of Hazardous Materials, 2024)

Elemental mercury removal by copper-containing brominated pyrolytic chars derived from waste printed circuit boards - Gan Wan; Tao Chen; Linlin Xu; Lushi Sun (Fuel, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

Boosting TNBC immune checkpoint blockade with an imaging-therapy coupled ozone delivery nano system - Linlin Song; Zhihui Liu; Xiujing He; Tianyue Xu; Meixu Chen; Zihan Xu; Haina Zhao; Jiaojiao Suo; Hong Wang; Zhankun Yang; Shenglan You; Xiaoting Chen; et al. (Chemical Engineering Journal, 2024)

An integrated investigation combining network pharmacology and computer simulation dissects the potential mechanism of anti-obesity of Monascus pigments (MPs) - Jiaxing Li; Huijing Zhang; Linlin Xu; Huiqian Liu; Chenchen Qi; Chengtao Wang; Wei Chen (Food Bioscience, 2024)

Intermittent irrigation as a solution for reduced emissions and increased yields in ratoon rice systems - Lang Zhang; Linlin Li; Qiyuan Tang; Huaqin Xu; Huabin Zheng; Faming Wang; Jianwu Tang (Plant and Soil, 2024)

Unraveling the dynamics of bed and breakfast clusters development: A multiscale analysis - Hu Yu; Linlin Xu (Applied Geography, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

Integrative proteomic-metabolomics strategy reveals the regulators and mechanism of enhancing cyclic lipopeptides in the high-cell-density fermentation of Bacillus subtilis S1702 - Bo Zhang; Linlin Xu; Hui Yang; Zhengjun Pang; Wenshuo Zhang; Fenghuan Wang; Huilin Liu; Junfeng Fan; Bolin Zhang (Process Safety and Environmental Protection, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Unprecedented recent warming as recorded by tree-ring in the western Qinling Mountains, China - Yiyun Yuan; Yang Deng; Linlin Gao; Xiyue Fu; Yanjun Xu; Xiaohua Gou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Experimental and theoretical studies on effective synergistic low-temperature removal of NO and typical volatile organic compounds (VOCs) from flue gas based on Cu@VWTi catalyst - Siyuan Lei; Lele Wang; Linlin Xu; Ben Wang; Lushi Sun (Journal of Cleaner Production, 2024)

Formation mechanism of polycyclic aromatic hydrocarbons during mineral oil pyrolysis: A ReaxFF molecular dynamics study - Linlin Xu; Gan Wan; Lushi Sun; Li Lin (Fuel, 2024)

Antimicrobial photodynamic inactivation pH-responsive films based on gelatin/chitosan incorporated with aloe-emodin - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Wei Ji; Baocai Xu; Hualin Wang (Food Chemistry, 2024)

Determination of chloropropanol esters and glycidyl esters in instant noodles based on solid-phase microextraction with chitosan-β-cyclodextrin coated fiber - Linlin Bian; Xue Ge; Senwei Feng; Guangxuan Chen; Kefeng Li; Xu Wang (Food Chemistry, 2024)

Imbalances in the gut microbiota and metabolome are associated with functional constipation in pregnancy - Ruili Pan; Ying Chen; Guopeng Lin; Haojue Wang; Xiaopeng Xu; Linlin Wang; Peijun Tian; Jianxin Zhao; Wei Chen; Gang Wang (Food Bioscience, 2024)

Photosynthetic microalgae microbial fuel cells for bioelectricity generation and microalgae lipid recovery using Gd-Co@N-CSs/NF as cathode - Linlin Qin; Yiming Qin; Na Cui; Xu Han; Haoran Lu; Tong Yang; Wenyan Liang (Chemical Engineering Journal, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

A review of indoor nitrous acid (HONO) pollution: Measurement techniques, pollution characteristics, sources, and sinks - Chang Liu; Linlin Liang; Wanyun Xu; Qingxin Ma (Science of The Total Environment, 2024)

Magnetite alleviating calcification of anaerobic granular sludge (AnGS): Electron transfer enhancement and ion competition - Linlin Chen; Ruoxuan Yuan; Xiangyang Xu; Liang Zhu (Science of The Total Environment, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Quantifying the environmental synergistic effect of cooling-air purification-carbon sequestration from urban forest in China - Rundong Feng; Shenghe Liu; Fuyuan Wang; Kaiyong Wang; Ping Gao; Linlin Xu (Journal of Cleaner Production, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

CO2 methanation reaction over La-modified NiAl catalysts derived from hydrotalcite-like precursors - Linlin Zhou; Xiaoming Guo; Xu Hu; Yaxin Zhang; Jinglin Cheng; Qiangsheng Guo (Fuel, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

Melatonin alleviates di-butyl phthalate (DBP)-induced ferroptosis of mouse leydig cells via inhibiting Sp2/VDAC2 signals - Si Yang; Meiwei Chen; Jiahui Meng; Chaoju Hao; Linlin Xu; Jinglei Wang; Jiaxiang Chen (Environmental Research, 2024)

Proteomic insights into the response of Halomonas sp. MNB13 to excess Mn(Ⅱ) and the role of H2S in Mn(Ⅱ) resistance - Xiuli Xu; Fuhang Song; Guoliang Zhang; Linlin Ma; Na Yang (Environmental Research, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Clinical Application of Polygenic Risk Score in IgA Nephropathy - Linlin Xu; Ting Gan; Pei Chen; Yang Liu; Shu Qu; Sufang Shi; Lijun Liu; Xujie Zhou; Jicheng Lv; Hong Zhang (Phenomics, 2024)

Revealing the degrading-possibility of methyl red by two azoreductases of Anoxybacillus sp. PDR2 based on molecular docking - Shulin Zhang; Linlin Feng; Yanyan Han; Zihang Xu; Luhui Xu; Xuejiao An; Qinghua Zhang (Chemosphere, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Kinetics and debromination studies on the pyrolysis of waste printed circuit boards with the addition of copper and copper oxides - Tao Chen; Chuan Ma; Ben Wang; Linlin Xu; Wu Yang; Lushi Sun (Journal of Cleaner Production, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

A prospective comparative study on bladder volume measurement with portable ultrasound scanner and CT simulator in pelvic tumor radiotherapy - Fei Bai; Qiuxia Hu; Xiaowei Yao; Ming Cheng; Lina Zhao; Linlin Xu (Physical and Engineering Sciences in Medicine, 2024)
Objective: The consistency of bladder volume is very important in pelvic tumor radiotherapy, and portable bladder scanner is a promising device to measure bladder volume. The purpose of this study was to investigate whether the bladder volume of patients with pelvic tumor treated with radiotherapy can be accurately measured using the Meike Palm Bladder Scanner PBSV3.2 manufactured in China and the accuracy of its measurement under different influencing factors. Methods: A total of 165 patients with pelvic tumor undergoing radiotherapy were prospectively collected. The bladder volume was measured with PBSV3.2 before simulated localization. CT simulated localization was performed when the bladder volume was 200-400ml. The bladder volume was measured with PBSV3.2 immediately after localization and recorded. The bladder volume was then delineated on CT simulation images and recorded. To compare the consistency of CT simulation bladder volume and bladder volume measured by PBSV3.2. To investigate the accuracy of PBSV3.2 in different sex, age, treatment purpose, and bladder volume. Results: There was a significant positive correlation with bladder volume on CT and PBSV3.2 ( r = 0.874; p < 0.001). The mean difference between CT measured values and PBSV3.2 was (-0.14 ± 50.17) ml. The results of the different variables showed that the overall mean of PBSV3.2 and CT measurements were statistically different in the age ≥ 65 years, bladder volumes > 400ml and ≤ 400ml groups ( p = 0.028, 0.002, 0.001). There was no statistical significance between the remaining variables. The volume difference between PBSV3.2 measurement and CT was 12.87ml in male patients, which was larger than that in female patients 3.27ml. Pearson correlation analysis showed that the correlation coefficient was 0.473 for bladder volume greater than 400ml and 0.868 for bladder volume less than 400ml; the correlation coefficient of the other variables ranged from 0.802 to 0.893. Conclusion: This is the first large-sample study to evaluate the accuracy of PBSV3.2 in a pelvic tumor radiotherapy population using the convenient bladder scanner PBSV3.2 made in China. PBSV3.2 provides an acceptable indicator for monitoring bladder volume in patients with pelvic radiotherapy. It is recommended to monitor bladder volume with PBSV3.2 when the planned bladder volume is 200-400ml. For male and patients ≥ 65 years old, at least two repeat measurements are required when using a bladder scanner and the volume should be corrected by using a modified feature to improve bladder volume consistency.

Distribution and influencing factors of macrobenthos on three seagrass beds in the intertidal zone of Shandong province, China - Yinglu Ji; Bo Song; Jiangling Xu; Shaoyu Jiang; Linlin Chen; Baoquan Li (Frontiers in Marine Science, 2024)
Introduction The macrobenthos plays a vital role within the ecosystem of seagrass beds, with its characteristics and spatial distribution serving as indicators of the well-being of the seagrass beds. Methods In August 2018, three seagrass beds located in the Yellow River Estuary of Dongying, the west coast of Yantai, and Swan Lake of Weihai, were investigated to compare the ecological influences of seagrass habitat on the benthic environment and macrobenthic community. Within each seagrass bed, porewater, sediment, and macrobenthos were sampled from three separate stations (center of seagrass bed, edge of seagrass bed and bare area). Results and discussion One-way ANOVA showed significant differences ( p < 0.05) in environmental factors and macrobenthos species, abundance, biomass and diversity indices among the three seagrass beds. The present data did not show significant impacts on habitat and macrobenthos in the different coverage areas of seagrass beds at the investigated spatial scales, though crustacea and some carnivores were relatively more inclined to inhabit areas with higher seagrass densities. Aquaculture and eutrophication may trigger the loss of seagrass bed habitats, that affects macrobenthic biodiversity, and conservation measures are needed to protect seagrass bed habitats.

A comprehensive study on the co-removal of Cr (VI) and ciprofloxacin via microbial-photocatalytic coupling: Mechanistic insights and performance evaluation - Yilin Dong; Qiuwen Wang; Jinyu Zhu; Linlin Liang; Dongyu Xu; Xueyue Mi; Zhijun Ren; Pengfei Wang (Journal of Environmental Management, 2024)

A copula-based parametric composite drought index for drought monitoring and applicability in arid Central Asia - Nanji Suo; Changchun Xu; Linlin Cao; Lingling Song; Xiaoni Lei (CATENA, 2024)

Comprehensive analyses of annexins in naked carp (Gymnocypris przewalskii) unveil their roles in saline-alkaline stress - Linlin A; Yujing Zhang; Baoke Xu; Haichen Zhang; Yixin Li; Le Wang; Jian Liang; Weiguo Zhou; Zhaohui Feng; Hong Zhang (Aquaculture, 2024)

Study on the late quaternary activity of the Jinyang-Ningnan segment of the Lianfeng fault zone - Liangliang Wu; Zhongtai He; Dongsheng Xu; Linlin Li; Long Guo; Xingao Li (Journal of Structural Geology, 2024)

Controllable synthesis of polyaspartic acid: Studying into the chain length effect for calcium scale inhibition - Meng-Long Zhang; Zheng Ruan; Yu Han; Zhi-Wei Cao; Linlin Zhao; Yuan-Qing Xu; Zhong-Yan Cao; Wen-Yan Shi; Ying Xu (Desalination, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

A novel lateral epitaxial Bi2O3@BiOCl heterostructure for photocatalytic antibiotic degradation in an internal circulation fluidized bed reactor - Yilin Dong; Shaoxuan Pang; Fuqiang Zhang; Dongyu Xu; Qiuwen Wang; Kang Wang; Lijun Zhang; Linlin Liang; Zhijun Ren; Pengfei Wang (Chemical Engineering Journal, 2023)

circ_SPEF2 Regulates the Balance of Treg Cells by Regulating miR-16-5p/BACH2 in Lymphoma and Participates in the Immune Response - Jie Zhou; Min Xu; ZhaoZhao Chen; LinLin Huang; ZhuoLin Wu; ZhongPei Huang; Lin Liu (Tissue Engineering and Regenerative Medicine, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Strategies for the coordinated control of particulate matter and carbon dioxide under multiple combined pollution conditions - Zhenyu Wang; Huan Zhao; Han Xu; Jie Li; Tong Ma; Linlin Zhang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

Assessment on the stereoselective behavior of cyflumetofen to earthworms (Eisenia foetida): Degradation, bioaccumulation, toxicity mechanism, and metabolites - Linlin Shi; Chao Shen; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Science of The Total Environment, 2023)

Synergistic strategy based on mild phototherapy and deep tumor hypoxia reversal comprehensively remodels the tumor microenvironment for improved immunotherapy - Linlin Tao; Gang Cheng; Fangnan Lv; Ruiqi Wang; Nan Yang; Zuhang Xing; Boyu Gu; Siyuan Meng; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

Paleoproterozoic skarn mineralization events and geodynamic background in the Jiao-Liao-Ji Belt: Geological, geochemical and chronological evidence from the Daqinggou Fe–Cu polymetallic deposit in Ji'an, NE China - YanPeng Liu; JingGui Sun; LinLin Wang; ZhiKai Xu; ChengLin Bai; Xiang Chang; TingTing Zhang (Precambrian Research, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Inequality and its driving forces in residential CO2 emission: Perspective of energy use pattern - Lei Chen; Linyu Xu; Yongyang Wang; Linlin Xia; Zhifeng Yang (Journal of Cleaner Production, 2023)

MiR-590-5p promotes cisplatin resistance via targeting hMSH2 in ovarian cancer - Bing Li; Xuejie Xu; Linlin Zheng; Xiaojie Jiang; Jing Lin; Guoliang Zhang (Molecular Biology Reports, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Evolution of the landscape pattern in the Xin'an River Basin and its response to tourism activities - Linlin Xu; Hu Yu; Linsheng Zhong (Science of The Total Environment, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Systematic assessment of cyflumetofen toxicity in soil-earthworm (Eisenia fetida) microcosms - Linlin Shi; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Journal of Hazardous Materials, 2023)

Glyphosate induces autophagy in hepatic L8824 cell line through NO-mediated activation of RAS/RAF/MEK/ERK signaling pathway and energy metabolism disorders - Linlin Zhang; Lu Chen; Meng Qi; Fuchang Yu; Xiaotong Ni; Haozheng Hong; Haotian Xu; Shiwen Xu (Fish & Shellfish Immunology, 2023)

Experimental investigation on seismic performance of self-centering frictional cast-in-situ beam-column joints - Xiao Lu; Hang Xu; Xuemin Zhang; Linlin Xie (Engineering Structures, 2023)

Occurrence, sources and risk of heavy metals in soil from a typical antimony mining area in Guizhou Province, China - Yuting Guo; Rongshan Wu; Changsheng Guo; Jiapei Lv; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2023)

Sources and historical records of metal(loid)s in river sediments from an agricultural tributary of Tuojiang river: Evidence from geochemical analyses and Pb isotope - Fen Xu; Rui Yang; Hong Wang; Xiaoxia He; Weiwei Li; Yao Wei; Linlin Bao; Jianfei Yuan; Hongjin Tong (Chemosphere, 2023)

Corrigendum to “Near-zero-waste hydrogenolysis of poly(lactic acid) to biofuel” [Fuel 334 (2022) 126609] - Jialin Xu; Kuo Zhou; Jinxia Fu; Zaiming Tan; Linlin Qin; Peigao Duan; Yongjun Xu; Shimin Kang (Fuel, 2023)

Real-time monitoring of mercury(II) in water and food samples using a quinoline-based ionic probe - Siying Che; Linlin Yin; Ming Chen; Yao Fan; Anni Xu; Chunsong Zhou; Haiyan Fu; Yuanbin She (Food Chemistry, 2023)

Allosteric synthetic antibody (Allo-SyAb) for improved cancer immunotherapy - Jiajing Chen; Mengchen Xu; Yongxin Zhang; Linlin Xu; Shuyue Zhao; Yingli An; Rujiang Ma; Yang Liu; Feihe Ma; Linqi Shi (Chemical Engineering Journal, 2023)

Bimetal Cu and Fe modified g-C3N4 sheets grown on carbon skeleton for efficient and selective photocatalytic reduction of CO2 to CO - Songyuan Bian; Xueyan Li; Long Zhang; Libin Wang; Jingzhen Wang; Qing Xu; Linlin Zang; Yanhong Zhang; Liguo Sun (Journal of Environmental Chemical Engineering, 2023)

Tannin alleviates glyphosate exposure-induced apoptosis, necrosis and immune dysfunction in hepatic L8824 cell line by inhibiting ROS/PTEN/PI3K/AKT pathway - Linlin Zhang; Lu Chen; Dayong Tao; Fuchang Yu; Meng Qi; Shiwen Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Long-term non-phosphorus application increased paddy methane emission by promoting organic acid and methanogen abundance in Tai Lake region, China - Chen Xu; Susu Shen; Beibei Zhou; Yuanyuan Feng; Zhu He; Linlin Shi; Yu Wang; Haihou Wang; Tripti Mishra; Lihong Xue (Science of The Total Environment, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Understanding the N-acylated homoserine lactones(AHLs)-based quorum sensing for the stability of aerobic granular sludge in the aspect of substrate hydrolysis enhancement - Zhiming Zhang; Linlin Wang; Yatong Ji; Runjuan Cao; Jiaheng Zhou; Mengyan Li; Liang Zhu; Xiangyang Xu (Science of The Total Environment, 2023)

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Near-zero-waste hydrogenolysis of poly(lactic acid) to biofuel - Jialin Xu; Kuo Zhou; Jinxia Fu; Zaiming Tan; Linlin Qin; Peigao Duan; Yongjun Xu; Shimin Kang (Fuel, 2023)

Metagenomic and extracellular polymeric substances analysis reveals the mechanism of exogenous N-hexanoyl-L-homoserine lactone in alleviating the inhibition of perfluorooctanoic acid on anammox process - Linqin Tang; Chengyuan Su; Cuiping Fan; Linlin Cao; Zhu Liang; Yufeng Xu; Zhengpeng Chen; Qing Wang; Menglin Chen (Bioresource Technology, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Synergistic relationship or not? Understanding the resilience and efficiency of the tourism economy: evidence from Hainan Province, China - Pengfei Zhang; Hu Yu; Linlin Xu; Wei Guo; Mingzhe Shen (Environment, Development and Sustainability, 2023)

RETRACTED: Study on the effect of SDBS and SDS on deep coal seam water injection - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Pahs emission characteristics and the mitigation in the valuable products from used mineral oil thermolysis recycling - Linlin Xu; Jie Yu; Gan Wan; Lushi Sun (Fuel, 2023)

Pseudo-isotopic substituted (Co0.5Ni0.5)S2 anchoring on V4C3T MXene as an efficient anode for full sodium-ions batteries - Yilin Li; J.M. Cao; Linlin Li; Zeyu Yuan; Dongdong Li; Junzhi Li; Yuming Zhang; Hao Xu; Wei Han; Lili Wang (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Combining microclimatic monitoring with questionnaires, for understanding thermal comfort in Linpan, a typical agricultural ecosystem settlement in the Chengdu plain - Linlin Chen; Gretchen Kalonji; Lilai Xu; Pufan Ma; Linmiao Hu (Building and Environment, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Investigation of the mechanism of copy number variations involving the α-globin gene cluster on chromosome 16: two case reports and literature review - Dina Zhu; Linlin Xu; Yanxia Zhang; Guanxia Liang; Xiaofeng Wei; Liyan Li; Wangjie Jin; Xuan Shang (Molecular Genetics and Genomics, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.

Operation performance of an ultralow-temperature cascade refrigeration freezer with environmentally friendly refrigerants R290-R170 - Haihui Tan; Lingfei Xu; Linlin Yang; Minkai Bai; Zhan Liu (Environmental Science and Pollution Research, 2022)

Alteration of alpha and beta diversity in nekton community by extreme marine heatwave events: An example from the East China Sea - Zunlei Liu; Linlin Yang; Liping Yan; Hui Zhang; Yi Zhang; Min Xu; Yan Jin; Jiahua Cheng (Frontiers in Marine Science, 2022)
In the year of 2016 to 2017, record-breaking marine heatwave (MHW) events occurred along the Chinese coast, exerting severe impacts on coastal fishes and fisheries. However, the response of the nekton community to MHW events still remains poorly understanding. Thus, to investigate the influences of the MHW events on species composition dynamics, this study conducted a survey on nekton communities in the northern East China Sea in the summers during 2014 to 2017. The recently-developed “heatwaveR” package was adopted to describe the variation characteristics of heatwaves within the study area, based on high-resolution remote-sensing sea surface temperature products. We also compared variations in the community structures of different biological groups before (2014–2015) and during the occurrence of the MHW events (2016–2017). During the MHW events, temperature increased by approximately 2.3°C in both 2016 and 2017. Compared with those before the MHW events, the biomass and dominance of several important crustaceans decreased, and the biomass of warm water affinity species increased significantly, while their richness and diversity decreased; the biomass of warm temperature affinity species declined significantly, while their diversity increased slightly. These results show the difference in the response rates of species with different thermal preferences and different species compositions to the extreme climate change. Beta diversity analysis revealed that the inter-group variation before and during the MHW event exceeded the intra-group variation, proving that MHWs changed the community structure to a certain extent. PERMANOVA test showed that the species compositions of planktivorous fish (FG1) and small-omnivorous fish (FG2) in the feeding-functional groups were significantly different before and during the MHW event, which may be attributed to the impact of MHWs on oligotrophic fishes through thermal preference and the trophic cascade effect. There was no significant change in the species compositions of other functional groups, indicating that medium-trophic and eutrophic fishes possessed certain adaptability to MHWs. Regarding fisheries management under extreme warming events, it would be advisable to diagnose temperature anomalies in the early stage, monitor changes in species abundance in the early life cycle, and then rapidly develop suitable fishing strategies.

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

Neutralization Activity of Anti-drug Antibodies Against a Biotherapeutic Can Be Predicted from a Comprehensive Pharmacokinetics, Pharmacodynamics, and Anti-drug Antibody Data Analysis - Weifeng Xu; Brian Maas; Brad Roadcap; Aparna Swarup; Thomas Steinmetz; Linlin Luo; Marina Ichetovkin; Sandra Wood; Faye Vazvaei-Smith; Andrew Wen-Tseng Lee; Kalpit Vora; Roy Helmy (The AAPS Journal, 2022)

Extensive Interspecific Gene Flow Shaped Complex Evolutionary History and Underestimated Species Diversity in Rapidly Radiated Dolphins - Weijian Guo; Di Sun; Yang Cao; Linlin Xiao; Xin Huang; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Mammalian Evolution, 2022)
Recently diverged taxa are often characterized by high rates of hybridization, which can complicate phylogenetic reconstruction. For this reason, the phylogenetic relationships and evolutionary history of dolphins are still not very well resolved; the question of whether the genera Tursiops and Stenella are monophyletic is especially controversial. Here, we performed re-sequencing of six dolphin genomes and combined them with eight previously published dolphin SRA datasets and six whole-genome datasets to investigate the phylogenetic relationships of dolphins and test the monophyly hypothesis of Tursiops and Stenella . Phylogenetic reconstruction with the maximum likelihood and Bayesian methods of concatenated loci, as well as with coalescence analyses of sliding window trees, produced a concordant and well-supported tree. Our studies support the non-monophyletic status of Tursiops and Stenella because the species referred these genera do not form exclusive monophyletic clades. This suggests that the current taxonomy of both genera might not reflect their evolutionary history and may underestimate their diversity. A four-taxon D -statistic (ABBA-BABA) test, five-taxon D FOIL test, and tree-based PhyloNet analyses all showed extensive gene flow across dolphin species, which could explain the instability in resolving phylogenetic relationship of oceanic dolphins with different and limited markers . This study could be a good case to demonstrate how genomic data can reveal complex speciation and phylogeny in rapidly radiating animal groups.

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Jiulin Chan; Wei Zhang; Yue Xu; Yu Xue; Linlin Zhang (Frontiers in Marine Science, 2022)
Genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasible in oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in Crassostrea gigas angulate . We identified the β-tubulin gene in the oyster genome and showed its spatiotemporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by Sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Moreover, the larval swimming behavior in the mutants was detected to be significantly decreased by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker gene, our study established CRISPR/Cas9-mediated mosaic mutagenesis technology based on electroporation, providing an efficient tool for gene function validation in the oyster. Moreover, our research also set up an example that can be used in genetic engineering breeding and productive traits improvement in oysters and other aquaculture species.

Bak interacts with AKT and is involved in TNFα/CHX-induced apoptosis - Jiayue Song; Fuqiang Zhang; Yu Wang; Yuxiang Wang; Jingtian Zhang; Zixuan Xiao; Xueqi Fu; Xuemin Xu; Linlin Zeng (Molecular and Cellular Biochemistry, 2022)

Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

Development of the CSOMIO Coupled Ocean-Oil-Sediment- Biology Model - Dmitry S. Dukhovskoy; Steven L. Morey; Eric P. Chassignet; Xu Chen; Victoria J. Coles; Linlin Cui; Courtney K. Harris; Robert Hetland; Tian-Jian Hsu; Andrew J. Manning; Michael Stukel; Kristen Thyng; et al. (Frontiers in Marine Science, 2021)
The fate and dispersal of oil in the ocean is dependent upon ocean dynamics, as well as transformations resulting from the interaction with the microbial community and suspended particles. These interaction processes are parameterized in many models limiting their ability to accurately simulate the fate and dispersal of oil for subsurface oil spill events. This paper presents a coupled ocean-oil-biology-sediment modeling system developed by the Consortium for Simulation of Oil-Microbial Interactions in the Ocean (CSOMIO) project. A key objective of the CSOMIO project was to develop and evaluate a modeling framework for simulating oil in the marine environment, including its interaction with microbial food webs and sediments. The modeling system developed is based on the Coupled Ocean-Atmosphere-Wave-Sediment Transport model (COAWST). Central to CSOMIO’s coupled modeling system is an oil plume model coupled to the hydrodynamic model (Regional Ocean Modeling System, ROMS). The oil plume model is based on a Lagrangian approach that describes the oil plume dynamics including advection and diffusion of individual Lagrangian elements, each representing a cluster of oil droplets. The chemical composition of oil is described in terms of three classes of compounds: saturates, aromatics, and heavy oil (resins and asphaltenes). The oil plume model simulates the rise of oil droplets based on ambient ocean flow and density fields, as well as the density and size of the oil droplets. The oil model also includes surface evaporation and surface wind drift. A novel component of the CSOMIO model is two-way Lagrangian-Eulerian mapping of the oil characteristics. This mapping is necessary for implementing interactions between the ocean-oil module and the Eulerian sediment and biogeochemical modules. The sediment module is a modification of the Community Sediment Transport Modeling System. The module simulates formation of oil-particle aggregates in the water column. The biogeochemical module simulates microbial communities adapted to the local environment and to elevated concentrations of oil components in the water column. The sediment and biogeochemical modules both reduce water column oil components. This paper provides an overview of the CSOMIO coupled modeling system components and demonstrates the capabilities of the modeling system in the test experiments.

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

A benchmark city for seismic resilience assessment - Qingxue Shang; Xiaodong Guo; Quanwang Li; Zhen Xu; Linlin Xie; Chaofeng Liu; Jichao Li; Tao Wang (Earthquake Engineering and Engineering Vibration, 2020)

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

Tissue distribution of transcription for 29 lipid metabolism-related genes in Takifugu rubripes, a marine teleost storing lipid predominantly in liver - Houguo Xu; Xiaoxue Meng; Linlin Jia; Yuliang Wei; Bo Sun; Mengqing Liang (Fish Physiology and Biochemistry, 2020)

Quality by Design–Based Assessment for Analytical Similarity of Adalimumab Biosimilar HLX03 to Humira® - Erhui Zhang; Liqi Xie; Peilan Qin; Lihong Lu; Yanpeng Xu; Wenyuan Gao; Linlin Wang; Michael Hongwei Xie; Weidong Jiang; Scott Liu (The AAPS Journal, 2020)
Quality by design (QbD) is an efficient but challenging approach for the development of biosimilar due to the complex relationship among process, quality, and efficacy. Here, the analytical similarity of adalimumab biosimilar HLX03 to Humira® was successfully established following a QbD quality study. Quality target product profile (QTPP) of HLX03 was first generated according to the public available information and initial characterization of 3 batches of Humira®. The critical quality attributes (CQAs) were then identified through risk assessment according to impact of each quality attribute on efficacy and safety. The anticipated range for each CQA was derived from similarity acceptance range and/or the corresponding regulatory guidelines. Finally, a panel of advanced and orthogonal physicochemical and functional tests and comparison of 6 batches of HLX03 and 10 batches of the reference standard demonstrated high similarity of HLX03 to Humira®, except for slightly lower percentage of high mannosylated glycans (%HM) in HLX03 which had no effect on FcγRIII binding and antibody-dependent cell-mediated cytotoxicity (ADCC) activity in human peripheral blood mononuclear cell (PBMC). All above demonstrated the feasibility and efficiency of QbD-based similarity assessment of a biosimilar monoclonal antibody (mAb).

Comparison of different soil dielectric models for microwave soil moisture retrievals - Linlin Zhang; Qingyan Meng; Die Hu; Ying Zhang; Shun Yao; Xu Chen (International Journal of Remote Sensing, 2020)

Different chemical composition and storage mechanism of soil organic matter between active and permafrost layers on the Qinghai–Tibetan Plateau - Yinghui Wang; Yunping Xu; Dandan Wei; Linlin Shi; Zehua Jia; Yuanhe Yang (Journal of Soils and Sediments, 2020)

Physiological responses of yellow-horn seedlings to high temperatures under drought condition - Hua Jin; Jixiang Zou; Linlin Li; Xinlei Bai; Tong Zhu; Junbao Li; Bingcheng Xu; Zhi Wang (Plant Biotechnology Reports, 2020)

Cloning and Characterization of Cholesterol 25-Hydroxylase (ch25h) From a Marine Teleost, Chinese Tongue Sole (Cynoglossus semilaevis), and Its Gene Expressions in Response to Dietary Arachidonic Acid - Houguo Xu; Bo Sun; Linlin Jia; Yuliang Wei; Zhangbin Liao; Mengqing Liang (Frontiers in Marine Science, 2020)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

Spatiotemporal evolution of C3/C4 vegetation and its controlling factors in southern China since the last glacial maximum - Linlin Cui; Jianfang Hu; Xu Wang (Science China Earth Sciences, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

A study of the coupled bioelectrochemical system-upflow anaerobic sludge blanket for efficient transformation of 2,4-dichloronitrobenzene - Hui Chen; Donghui Lu; Linlin Chen; Caiqin Wang; Xiangyang Xu; Liang Zhu (Environmental Science and Pollution Research, 2019)

Xylitol Production by Candida tropicalis 31949 from Sugarcane Bagasse Hydrolysate - Linlin Xu; Lei Liu; Sijia Li; Wenjing Zheng; Yuanyuan Cui; Rong Liu; Weidong Sun (Sugar Tech, 2019)

Contribution of heterotrophic bacterioplankton to cyanobacterial bloom formation in a tributary backwater area of the Three Gorges Reservoir, China - Lunhui Lu; Linlin Xu; Jixiang Yang; Zhe Li; Jinsong Guo; Yan Xiao; Juanjuan Yao (Environmental Science and Pollution Research, 2018)

Fermentation Kinetics of Enzymatic Hydrolysis Bagasse Solutions for Producing l-Lactic Acid - Yuanyuan Cui; Rong Liu; Linlin Xu; Wenjing Zheng; Weidong Sun (Sugar Tech, 2018)

Difference of acute dissociation and 1-day culture on the electrophysiological properties of rat dorsal root ganglion neurons - Yuanlong Song; Miaomiao Zhang; Xiaoqing Tao; Zifen Xu; Yunjie Zheng; Minjie Zhu; Liangpin Zhang; Jinhan Qiao; Linlin Gao (Journal of Physiology and Biochemistry, 2018)

Adsorptive removal of organics from aqueous phase by acid-activated coal fly ash: preparation, adsorption, and Fenton regenerative valorization of “spent” adsorbent - Nannan Wang; Linlin Hao; Jiaqing Chen; Qiang Zhao; Han Xu (Environmental Science and Pollution Research, 2018)

Labile organic carbon fractions and carbon pool management index in a 3-year field study with biochar amendment - Xu Yang; Di Wang; Yu Lan; Jun Meng; Linlin Jiang; Qiang Sun; Dianyun Cao; Yuanyuan Sun; Wenfu Chen (Journal of Soils and Sediments, 2018)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Applicability of TRMM satellite precipitation in driving hydrological model for identifying flood events: a case study in the Xiangjiang River Basin, China - Yumeng Yang; Juan Du; Linlin Cheng; Wei Xu (Natural Hazards, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Selenium Deficiency Influences the Expression of Selenoproteins and Inflammatory Cytokines in Chicken Aorta Vessels - Qiang Du; Haidong Yao; Linlin Yao; Ziwei Zhang; Xingen Lei; Shiwen Xu (Biological Trace Element Research, 2016)

Tree‐ring recorded drought variability in the northern Min Mountains of northwestern China - Yang Deng; Xiaohua Gou; Linlin Gao; Fen Zhang; Xiangyu Xu; Meixue Yang (International Journal of Climatology, 2016)
Drought is a recurrent natural disaster in northwestern China and it can have a substantial impact on the affected region; therefore, knowledge of drought variability is very important for drought adaptation and mitigation. However, the observed climate data are generally limited in length, which may hamper our understanding the full range of drought variability. Using tree‐ring width measurements of 155 series from 81 Pinus tabulaeformis trees at three sites in the northern Min Mountains of northwestern China, the standardized precipitation evapotranspiration index ( SPEI ) for May–August from 1804 to 2011 were reconstructed, which account for 64.8% of the variance in the instrumental record over 1954–2011. The new reconstruction is generally consistent with other moisture reconstructions nearby. Two notable features of the SPEI reconstruction is the severe drought starting in the late 1990s and the gradual drying trend since 1954. These features are also apparent in areas located in the north boundaries of Eastern Asian Summer Monsoon ( EASM ), which indicates that the study area may be affected by the EASM .

Role of Exogenous Nitric Oxide in Alleviating Iron Deficiency Stress of Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Yiling Song; Xiaoying Bai; Xianyi Tian; Linlin Xu; Shuang Liu; Zhenli He (Journal of Plant Growth Regulation, 2016)

Forward modeling analyses of Qilian Juniper (Sabina przewalskii) growth in response to climate factors in different regions of the Qilian Mountains, northwestern China - Junzhou Zhang; Xiaohua Gou; Yongxiang Zhang; Ming Lu; Xiangyu Xu; Fen Zhang; Wenhuo Liu; Linlin Gao (Trees, 2016)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

Roles of oxidative stress and endoplasmic reticulum stress in selenium deficiency-induced apoptosis in chicken liver - Linlin Yao; Qiang Du; Haidong Yao; Xi Chen; Ziwei Zhang; Shiwen Xu (BioMetals, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

Effects of Exogenous Salicylic Acid on Alleviating Chlorosis Induced by Iron Deficiency in Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Linlin Xu; Shuang Liu; Xiaoying Bai (Journal of Plant Growth Regulation, 2014)

Selenium Deficiency Influences the Gene Expressions of Heat Shock Proteins and Nitric Oxide Levels in Neutrophils of Broilers - Xi Chen; Haidong Yao; Linlin Yao; Jinxin Zhao; Yilin Luan; Ziwei Zhang; Shiwen Xu (Biological Trace Element Research, 2014)

Expression of tomato SlTIP2;2 enhances the tolerance to salt stress in the transgenic Arabidopsis and interacts with target proteins - Shichao Xin; Guohong Yu; Linlin Sun; Xiaojing Qiang; Na Xu; Xianguo Cheng (Journal of Plant Research, 2014)

A KPCA texture feature model for efficient segmentation of RADARSAT-2 SAR sea ice imagery - Linlin Xu; Jonathan Li; Alexander Wong; Cheng Wang (International Journal of Remote Sensing, 2014)

Effects of Exogenous Salicylic Acid and Nitric Oxide on Physiological Characteristics of Perennial Ryegrass Under Cadmium Stress - Quanhui Wang; Xue Liang; Yuanjie Dong; Linlin Xu; Xiuwei Zhang; Jing Kong; Shuang Liu (Journal of Plant Growth Regulation, 2013)

Fosmid library construction and end sequences analysis of the Pacific oyster, Crassostrea gigas - Linlin Zhang; Li Li; Fei Xu; Haigang Qi; Xiaotong Wang; Huayong Que; Guofan Zhang (Molluscan Research, 2013)

Overexpression of GbWRKY1 positively regulates the Pi starvation response by alteration of auxin sensitivity in Arabidopsis - Li Xu; Li Jin; Lu Long; Linlin Liu; Xin He; Wei Gao; Longfu Zhu; Xianlong Zhang (Plant Cell Reports, 2012)

Expression of phytoene synthase gene (Psy) is enhanced during fruit ripening of Cara Cara navel orange (Citrus sinensis Osbeck) - Nengguo Tao; Zhiyong Hu; Qin Liu; Juan Xu; Yunjiang Cheng; Linlin Guo; Wenwu Guo; Xiuxin Deng (Plant Cell Reports, 2007)